Direct Catalytic Asymmetric Mannich‐Type Reaction of α‐N3 Amide. Issue 49 (20th October 2015) - Sun, Zhongdong; Weidner, Karin; Kumagai, Naoya; Shibasaki, Masakatsu
Abstract: An α‐N3 7‐azaindoline amide serves as a latent enolate to directly engage in an asymmetric Mannich‐type reaction with N ‐thiophosphinoyl imines by the action of a cooperative catalyst. The thus‐obtained highly enantioenriched anti ‐adduct was transformed into β‐amino‐α‐azido acid in high yield by simple acidic treatment. Abstract : Take it easy : An α‐N3 7‐azaindoline amide serves as a latent enolate to directly engage in an asymmetric Mannich‐type reaction with N ‐thiophosphinoyl imines by the action of a cooperative catalyst. The thus‐obtained highly enantioenriched anti ‐adduct was transformed into β‐amino‐α‐azido acid in high yield by simple acidic treatment.